Ta có : \(\frac{AB}{3}=\frac{AC}{7}\Rightarrow\frac{AB^2}{9}=\frac{AC^2}{49}\) \(\Rightarrow\frac{\frac{1}{9}}{\frac{1}{AB^2}}=\frac{\frac{1}{49}}{\frac{1}{AC^2}}\)
Mặt khác, ta có \(\frac{1}{AB^2}+\frac{1}{AC^2}=\frac{1}{AH^2}=\frac{1}{42^2}\)
\(\Rightarrow\frac{\frac{1}{9}}{\frac{1}{AB^2}}=\frac{\frac{1}{49}}{\frac{1}{AC^2}}=\frac{\frac{1}{9}+\frac{1}{49}}{\frac{1}{AB^2}+\frac{1}{AC^2}}=\frac{\frac{58}{441}}{\frac{1}{42^2}}=232\)
\(\Rightarrow\begin{cases}AB^2=2088\\AC^2=11368\end{cases}\) \(\Rightarrow\begin{cases}AB=6\sqrt{58}\\AC=14\sqrt{58}\end{cases}\)
Vậy ............................................